Combination of Moringa Leaves Mask (Moringa Oleifera L.) and Butterfly Pea Flower Mask (Clitorea Ternatea L.) Plus Honey for Face Skin Moisture - Soekanto, Ayly; Tania, Putu Oky Ari; Al Aska, Andra Agnez; Hardiyono, Hardiyono (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Facial skin care is needed to maintain and preserve moisture and elasticity of the facial skin. The use of organic masks can be used to treat and provide nutrition to the facial skin to overcome facial skin problems. Objective: The purpose of this study was to measure effectiveness of the combination of moringa leaves mask (Moringa oleifera L.) and honey with butterfly pea flower mask (Clitorea ternatea L.) on facial skin moisture. Methods: The research is an analytical experimental study, 30 women aged 40-50 years old were given a combination of moringa leaves mask and honey on the right side of the face and butterfly pea flower mask and honey on the left side of the face, then before using the mask and after using the mask, the moisture value of the facial skin was measured with a skin moisture analyzer. The treatment in this study was given twice a week for three weeks, from April to May 2025 at the Wijaya Surabaya doctor's practice and clinic, using statistical analysis of the Pearson Correlation test with a p value of 0.000 (α <0.005). Result: The combination of moringa leaves and honey experienced an increase in moisture value of 70% moist skin and 30% normal skin, and the combination of butterfly pea flower mask and honey experienced an increase of 60% moist skin and 40% to normal skin. Conclusion: The combination of moringa leaves mask and honey with butterfly pea flower mask and honey only has a difference of 10%, meaning that the use of both combinations of these masks is equally useful in increasing moisture in facial skin.